Fatimah in Nusantara - Wendy Mukherjee (Universiti Kebangsaan Malaysia, 2005)
Fatimah, the daughter of the Prophet, wife of Ali and mother of Hasan and Husain presents the perfect traditional model of a Muslim woman. Politically, she continued the Prophet’s blood line and is the mother of the imams of Shi’ism. She is also held up as a spiritual example for her virtues of patience and compassion to those around her. Most Islamic manuscript literatures of Malaysia and Indonesia contain texts which tell of these virtues. The texts entered the archipelago with Islam itself and were preserved up to the beginning of print culture around 1920. This article describes the history of texts dealing with Fatimah in Nusantara